More Than Just a Target: Building a Healthy and Productive Organization - Sumarno, Sumarno (PT. Anagata Sembagi Education, 2025)
Organizational success has often been narrowly defined by financial targets and performance indicators, yet sustainable achievement requires a broader focus on organizational health. This study aims to explore how organizational health is conceptualized and practiced holistically within organizations, particularly across four dimensions: leadership, organizational culture, employee well-being, and psychological safety. Using a qualitative multiple case study design, data were collected through semi-structured interviews, focus group discussions, and document analysis from selected organizations in Indonesia. Thematic analysis was applied to identify recurring patterns and generate cross-case themes. The findings reveal that leadership serves as the cornerstone of organizational health, with supportive and empathetic behaviors fostering trust, engagement, and motivation. Organizational culture provides the collective framework, where collaboration and inclusivity translate health-related values into daily practices. Employee well-being is widely recognized but often constrained by workload pressures and policy–practice gaps, while psychological safety emerges as the critical enabler that transforms engagement into innovation and sustainable productivity. The study concludes that organizational health is a multidimensional construct achieved when leadership, culture, well-being, and psychological safety are aligned and mutually reinforcing. This holistic integration allows organizations to move beyond targets toward resilience, adaptability, and long-term performance.